2020
DOI: 10.18488/journal.61.2020.83.394.404
|View full text |Cite
|
Sign up to set email alerts
|

The Uniqueness of Flipped Learning Approach

Abstract: Pedagogical changes and adaptation of new models in teaching and learning should be considered as a means to develop a nation. One of the most popular growing models is flipped learning. Flipped learning is widely used all over the world in the teaching of different fields and subjects. It promotes meaningful learning, more student-centered rather than teacher-centered and is commonly aided with technological equipment such as pre-recorded videos, mobile apps or simply watching videos on YouTube before coming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Finally, the results of the interviews showed that most of the students were positive about the process of presenting and solving problems in front of classmates, which helped them to understand more detail in terms of electronics. Our findings are also in line with previous [ 25 , 28 , 29 ] who suggested that through cooperative learning, group learning and sharing can leverage learning difficulties and increase group interaction.…”
Section: Data Analysis and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, the results of the interviews showed that most of the students were positive about the process of presenting and solving problems in front of classmates, which helped them to understand more detail in terms of electronics. Our findings are also in line with previous [ 25 , 28 , 29 ] who suggested that through cooperative learning, group learning and sharing can leverage learning difficulties and increase group interaction.…”
Section: Data Analysis and Discussionsupporting
confidence: 93%
“…Above finding is consistent with Ozdamli, Fezile, and Gulsum Asiksoy [ 25 ] that there are also certain students who decline to do homework, whether it is worksheet or a video lesson. Although previous studies have proven that students have merely 10 minutes of the introduction of a new topic before they lose interest [ 26 , 27 , 28 ]. Thus, we suggest that pre-recording video lesson should be limited as short minutes as possible.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Several studies have been conducted on teachers' perceptions of the implementation of flipped classroom (Ansori & Nafi', 2019;Gough et al, 2017;Khaled, 2019;Yang, 2017;Yang & Chen, 2020). However, according to Rahman et al (2020), the studies conducted on flipped learning in Malaysia are fewer in number compared to the studies conducted around the globe.…”
Section: Introductionmentioning
confidence: 99%
“…The students and teachers of rural schools are often left out due to their lack of technologies and facilities. Hence, this study was aimed at exploring Malaysian ESL teachers' general perceptions of the implementation of the flipped classroom approach in their daily teaching processes; this was accomplished through a survey and an openended question, and teachers from rural areas were particularly focused on as the studies conducted involving them are still few (Rahman et al, 2020). As the focus was on schools in rural areas, problems such as lack of ICT and infrastructure were expected to be the challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Flipped learning is one of the growing technology-integrated teaching approaches that categorised under blended learning (Rahman, Yunus, & Hashim, 2020). It was introduced by Jonathan Bergmann and Aaron Sams in 2007 because their students could not come to class due to training and tournaments.…”
Section: Introductionmentioning
confidence: 99%